Untypical tuneable emission activated by NIR radiation observed in gadolinium borate nanomaterials doped with Yb3+, Ho3+ and Ce3+ ions - Agata Szczeszak; Justyna Czajka (Scientific Reports)
Abstract New luminescent nanoparticles with adjustable emission properties were synthesized via a hydrothermal method to investigate the effect of Ce3+ concentration on the tuneable emission properties of Yb3+/Ho3+ co-doped gadolinium borates. The synthesized samples’ comprehensive structural and morphological analysis was conducted utilizing X-ray diffraction and transmission electron microscopy. To obtain highly crystalline nanoparticles GdBO3:Yb3+/Ho3+/Ce3+ characterized by intense and bright emission, they were annealed at 525 °C and 925 °C. Under the excitation of 972 nm, the tunable yellow to green up-conversion (UC) emission was observed, while the Ce3+ concentration increased. This change correlated with a difference in the correlated color temperature from 4345 K to 5442 K, respectively. The untypical changes observed in the red-to-green (R/G) ratio, displaying a declining trend contrary to conventional expectations, allowed for the proposed mechanism for understanding their UC luminescence properties. The results obtained indicate that the Ce3+ doped GdBO3:Yb3+/Ho3+ nanoparticles demonstrate high application potential for anti-counterfeiting.